Strengths based leadership : great leaders, teams, and why people follow - Rath, Tom, 1975-; Conchie, Barry (New York : Gallup Press, 2008)
Two leadership consultants identify three keys to being a more effective leader: knowing your strengths and investing in others' strengths, getting people with the right strengths on your team, and understanding and meeting the four basic needs of those who look to you for leadership.
Includes bibliographical references (p. 259-266)
Keywords: Leadership; Self-realization